2013
DOI: 10.3892/ol.2013.1678
|View full text |Cite
|
Sign up to set email alerts
|

Renal myopericytoma: A case report with a literature review

Abstract: Myopericytoma is a rare neoplasm that generally arises from the skin and superficial soft tissues of distal extremities, and is particularly rare in the visceral organs. The current report presents a case of giant myopericytoma showing kidney involvement, which is extremely rare. A 39-year-old male presented to the Department of Urology with a 2-month history of a painless and palpable mass in the region of the left abdomen. Unenhanced computed tomography revealed a 9×10×18-cm3 mass that was heterogeneous with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…However, it most commonly occurs in young patients within the superficial soft tissues of the lower extremity. Deep-seated, visceral, and intracranial sites of disease are extremely rare [2] , [4] , [5] , [6] , [7] , [8] , [9] . Clinically, myopericytoma most often presents as a solitary, well-demarcated, slow-growing, and non-painful palpable nodule or soft tissue mass present for several years [3] , [4] , [10] .…”
Section: Discussionmentioning
confidence: 99%
“…However, it most commonly occurs in young patients within the superficial soft tissues of the lower extremity. Deep-seated, visceral, and intracranial sites of disease are extremely rare [2] , [4] , [5] , [6] , [7] , [8] , [9] . Clinically, myopericytoma most often presents as a solitary, well-demarcated, slow-growing, and non-painful palpable nodule or soft tissue mass present for several years [3] , [4] , [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Conventional CT examinations found that the lesions were usually isodense or hypodense, homogeneous or heterogeneous, occasionally calcified, and clearly bounded [ 14 , 18 , 20 24 ]. In contrast-enhanced CT scans, lesions were shown as homogeneous with severe enhancement [ 5 , 17 20 ] or peripheral enhancement [ 5 , 14 , 15 , 22 ]. Small vessels may be seen around the lesion [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to previous reports, the contrast-enhanced CT images of myopericytoma generally have a similar pattern. The tumors appear to be low-density lesions in the non-enhanced phase; however, the peripheral area of the tumor could be enhanced, showing rim-like enhancement in the arterial phase (11)(12)(13)(14)(15)(16). Small tumors are displayed as full-tumor enhancement in the arterial phase (13).…”
Section: Discussionmentioning
confidence: 99%